What to do with Marx's writings on art and aesthetics? : The mode of presentation and its limitations - Durán Medraño, José María (2025)
Marx’s fragments on art and aesthetics are a theoretical problem. The text argues that the interpretations of these fragments to date do not do justice to Marx’s theoretical edifice. It proposes to read Marx in a way that makes us reflect on the need to open up a new field of research. To this end, it makes use of the concepts and categories that Marx develops in the critique of political economy in a way that completes the fragments on art and aesthetics and transforms them into a materialist theory of art.